2014
DOI: 10.1016/j.neuroimage.2014.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Improving diffusion-weighted imaging of post-mortem human brains: SSFP at 7T

Abstract: Post-mortem diffusion imaging of whole, human brains has potential to provide data for validation or high-resolution anatomical investigations. Previous work has demonstrated improvements in data acquired with diffusion-weighted steady-state free precession (DW-SSFP) compared with conventional diffusion-weighted spin echo at 3 T. This is due to the ability of DW-SSFP to overcome signal-to-noise and diffusion contrast losses brought about by tissue fixation related decreases in T2 and ADC. In this work, data of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(80 citation statements)
references
References 50 publications
1
79
0
Order By: Relevance
“…For dwSTE and dwSSFP, the move to UHF is more beneficial, providing more SNR/unit time than 3 T. This is because T 2 (which dominates dwSE) decreases, but T 1 increases, which is leveraged in SSFP and stimulated echo acquisition mode (STEAM). In a comparison study, dwSSFP was found to have considerably higher SNR/unit time at 7 T compared with 3 T and to achieve excellent quality diffusion imaging at 7 T in post‐mortem, whole human brains . Using dwSTE at 9.4 T, high‐quality whole ex vivo human brain dMRI was reported at 400 μm isotropic …”
Section: Ex Vivo Diffusion Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…For dwSTE and dwSSFP, the move to UHF is more beneficial, providing more SNR/unit time than 3 T. This is because T 2 (which dominates dwSE) decreases, but T 1 increases, which is leveraged in SSFP and stimulated echo acquisition mode (STEAM). In a comparison study, dwSSFP was found to have considerably higher SNR/unit time at 7 T compared with 3 T and to achieve excellent quality diffusion imaging at 7 T in post‐mortem, whole human brains . Using dwSTE at 9.4 T, high‐quality whole ex vivo human brain dMRI was reported at 400 μm isotropic …”
Section: Ex Vivo Diffusion Acquisitionmentioning
confidence: 99%
“…In a comparison study, dwSSFP was found to have considerably higher SNR/unit time at 7 T compared with 3 T and to achieve excellent quality diffusion imaging at 7 T in post-mortem, whole human brains. 15 Using dwSTE at 9.4 T, high-quality whole ex vivo human brain dMRI was reported at 400 μm isotropic. 37…”
Section: Diffusion Weighting Preparationmentioning
confidence: 99%
“…Previous work (Foxley et al, 2014a) demonstrated that with a one-flip angle DW-SSFP acquisition, angular uncertainty in PDD estimates was reduced by increasing field strength from 3T to 7T, providing motivation to move to higher field when performing tractography. This reduction in uncertainty would be expected in local regions of tissue due to the higher SNR associated with an increase in field strength, but would be mitigated by the B1 effects considered in this work (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Ultra-high field scanners have potential to enable further gains in spatial resolution, with DW-SSFP providing a valuable tool for addressing the even shorter T2 values at 7T and above (Foxley et al, 2014a). However, DW-SSFP data acquired at 7T are compromised by B1 inhomogeneity (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion imaging contributes to the understanding of the macroscopic connectivity at the millimeter scale in the living brain, while postmortem diffusion tensor imaging studies already report isotropic resolutions of 1 mm in whole human brains down to 43 microns in rat brains [1]. Hence, not surprisingly, diffusion imaging is of great appeal to neuroscientists as a method for the visualization of connectivity patterns in both clinical and basic research.…”
mentioning
confidence: 99%